1991
DOI: 10.1111/j.1365-2141.1991.tb04451.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of recombinant human granulocyte colony‐stimulating factor in the myelodysplastic syndromes

Abstract: We conducted a phase II study of the intravenous administration of a glycosylated recombinant human granulocyte colony-stimulating factor (rhG-CSF) for 7-14 d in 41 patients with the myelodysplastic syndromes (MDS). Administration of rhG-CSF elicited striking rises in both leucocyte and neutrophil counts in the majority of the patients irrespective of the FAB subtypes of MDS. The rises in neutrophil counts were dose dependent and 5 micrograms/kg/d of rhG-CSF yielded approximately an 8-fold increase in neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Granulocytecolony-stimulating factor (G-CSF) and granulocyte macrophagecolony-stimulating factor (GM-CSF) increase neutrophil counts, do not increase the risk for leukemia, and have no effect on survival. [2][3][4] When combined with myeloid cytokines, rHuEPO can have synergistic effects on erythropoiesis in vitro. 5,6 Some clinical studies have shown that the combination of rHuG-CSF and rHuEPO has a better response rate (40%-50%) than rHuEPO alone.…”
mentioning
confidence: 99%
“…Granulocytecolony-stimulating factor (G-CSF) and granulocyte macrophagecolony-stimulating factor (GM-CSF) increase neutrophil counts, do not increase the risk for leukemia, and have no effect on survival. [2][3][4] When combined with myeloid cytokines, rHuEPO can have synergistic effects on erythropoiesis in vitro. 5,6 Some clinical studies have shown that the combination of rHuG-CSF and rHuEPO has a better response rate (40%-50%) than rHuEPO alone.…”
mentioning
confidence: 99%
“…The majority of MDS patients with neutropenia respond to G-CSF (Kobayashi et al, 1989;Yoshida et al, 1991;Kaczmarski et al, 1993;.…”
Section: Erythropoiesis Stimulating Agents (Esa)mentioning
confidence: 99%
“…It has been suggested that rHuG-CSF should be considered when there is no response to EPO after 6-8 weeks of therapy (Steensma et al, 2006). It has not been shown yet that rhG-CSF alone can improve survival in MDS patients (Kobayashi et al, 1989;Negrin et al, 1989;Ohyashuki et al, 1989;Negrin et al, 1990;Yoshida et al, 1991;Kaczmarski 1993). In association with a hypomethylating agent or lenalidomide or in case of severe infection, G-CSF can be used for the management of neutropenia after chemotherapy.…”
Section: Granulocyte Colony-stimulating Factor (G-csf)mentioning
confidence: 99%
“…The gene coding granulocyte colonystimulating factor (G-CSF) is located on chromosome 17ql 1.2 to 21, proximal to the breakpoint oft(15;17) in APL (8). During treatment with G-CSF, an increase in neutrophil counts is observed in patients with MDS, and in someof these patients increases in reticulocytes, and platelets counts have also been found (9,10). ATRAshows a synergistic effect with G-CSFon several leukemia cells in vitro (1 1).…”
Section: Several Investigatorsmentioning
confidence: 99%